Cytology’s New Frontier: The Sydney System’s Innovative Approach to Lymph Node Diagnosis - Nidhi Choudhari; Meghashree V; Vidhya Subramaniam; Sudha M; Prajna K S (GAIMS Journal of Medical Sciences)
Background: FNAC is the first diagnostic step in patients with lymphadenopathy because of its simplicity and minimal invasive nature which helps to confirm the clinical suspicion. A definite specific diagnosis may not be possible in a few cases but a categorization of disease and differential diagnosis can help suggest the most efficient further investigations, saving time and resources. The aim of this study was to ascertain the system’s applicability and precision in the diagnosis of lymph node cytology.